MAP of Tuberculosis Incidence in West Java Province in 2023 - Fondariesta Wulandini; Ema Hermawati; Melly Wulandari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Indonesia has various infectious diseases, one of which is tuberculosis. This disease is caused by a pathogenic agent, namely the bacteria Mycobacterium tuberculosis, which can cause primary symptoms such as a continuous cough. West Java Province is ranked first in the most TB cases in Indonesia, with a total of 203,226 cases in 2023. This study aims to map the spread of the disease by describing the distribution of tuberculosis cases and mapping the level of vulnerability through tuberculosis risk factors. The method used is a descriptive research on the Geographic Information System (GIS) approach with scoring techniques. The data used is in the form of secondary data from the official website (open data access) of the Central Statistics Agency (BPS) of West Java Province. After the collection of variable data from BPS, it is then analyzed with shapefile spatial data through the QGIS program software. The results of this study show that of the 27 districts/cities in West Java Province, there are 2 areas, namely Bogor Regency and Bekasi City, which have a very high level of vulnerability. This vulnerability overview is expected to be the government's initial step in efforts to control and prevent tuberculosis incidents through case detection, strengthening TB prevention programs and establishing cross-sectoral cooperation related to TB incidence, especially in high-risk areas.